Démarche d’investigation et explication au collège - Francesca Morselli; Elisabetta Panucci; Monica Testera (Recherches en Éducation)
We present a special case of inquiry based learning implemented in Italy in lower secondary school, the « Investigation and explanation activities ». At first we present the theoretical framework for the planning and implementation of the activities: the fonctions of explanation and the construct of rational behaviour. Afterwards, we present and analyze (by means of the theoretical tools) some episodes from a teaching experiment on isoperimetric rectangles. With this article we aim at contributing to the debate on inquiry based learning. More specifically, we tackle two crucial issues: how to characterize the tasks and questions to be posed during inquiry based learning activities; how to charaterize the roles of teachers, stduents and researchers.